2020
DOI: 10.31814/stce.nuce2020-14(3)-04
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cementless eco-binder as an alternative to traditional Portland cement in construction activities

Abstract: In this research, the performance of a cementless eco-binder, a mixture of waste materials including slag, circulating fluidized bed combustion ash (CFA), and rice husk ash (RHA) was investigated, in which CFA acted as an activator. One hundred and twenty paste samples were prepared by using the RHA/(slag + RHA) ratios of 0, 15, 30, 45% while keeping a constant ratio of CFA/(slag + RHA) at 25%. The setting period, compressive strength, the ultrasonic pulse velocity (UPV), and drying shrinkage of paste samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Nevertheless, cement production causes unexpected problems for the environment, which has received much attention in recent years. In detail, producing PC emits a high amount of carbon dioxide into the environment [4,5] as the progress of making 1 ton of PC discharges about 1 ton of carbon dioxide [6]. In addition, the production process of PC consumes a large amount of energy (about 1800 MJ for every ton of clinker [7] and about 3500 MJ for every ton of PC produced [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, cement production causes unexpected problems for the environment, which has received much attention in recent years. In detail, producing PC emits a high amount of carbon dioxide into the environment [4,5] as the progress of making 1 ton of PC discharges about 1 ton of carbon dioxide [6]. In addition, the production process of PC consumes a large amount of energy (about 1800 MJ for every ton of clinker [7] and about 3500 MJ for every ton of PC produced [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Re-utilization of these kinds of wastes as usable construction materials is an effective approach and also further brings economic benefits. In Vietnam, for instance, several studies have carried out to investigate the application of various industrial wastes such as unground rice husk ash [7], fly ash and residual rice husk ash [8], ground granulated blastfurnace slag, and circulating fluidized bed combustion ash [9] as construction materials. However, the use of waste bottom ash from incineration plants (IBA) as source material for producing construction materials has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies investigated the use of rice husk as a component in fired -clay bricks [18][19][20][21], others used rice husk ash in the production of unburnt bricks [1,22]. It is noticed that ground rice husk ash can be used as binder materials [1,[22][23][24], whereas unground rice husk ash can be used as fine aggregate [1,22]. Most of test results indicated that both the unit weight and compressive strength of bricks reduced, but the water absorption of bricks increased with the increase in rice husk content.…”
Section: Introductionmentioning
confidence: 99%